Dexmedetomidine nasal spray to treat high-activity postoperative delirium: a case report - Liu, Yujing; Chen, Lin; Liu, Qian; Li, Peng (Frontiers in Medicine, 2025)
High-activity postoperative delirium (POD) represents a prevalent neuropsychiatric complication during the perioperative period. Current clinical research predominantly focuses on preventive strategies, while effective pharmacological interventions remain limited, particularly for acute high-active subtypes. This case report demonstrates the successful use of dexmedetomidine nasal spray in managing acute high-active POD. The dexmedetomidine exerts its therapeutic effects through selective modulation of the locus coeruleus-noradrenergic pathway, providing physiological sedation resembling natural sleep architecture while preserving respiratory stability. It also exerts analgesic and anti-inflammatory effects. The nasal spray facilitated precise dosing with rapid symptom resolution and maintained hemodynamic stability. This novel approach offers a safe and effective way to manage acute high-active POD.